2009
DOI: 10.1007/s10295-009-0537-8
|View full text |Cite
|
Sign up to set email alerts
|

Change in the community structure of ammonia-oxidizing bacteria in activated sludge during selective incubation for MPN determination

Abstract: We investigated the changes in the community structure of ammonia-oxidizing bacteria (AOB) in activated sludge during incubation of the sludge in a medium selective for AOB. The number of AOB present in the activated sludge sample was enumerated by the most-probable-number (MPN) method. Both the activated sludge sample and the incubated samples for MPN determination were analyzed by polymerase chain reaction and denaturing gradient gel electrophoresis (PCR-DGGE). Universal PCR-DGGE indicated that even after 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…Nitrifying bacteria support the growth of heterotrophic bacteria via production of soluble microbial products and biomass decay [51], e.g., in low nutrient containing environments (such as in this study the examined drinking water and nitrifying enrichment samples). However, the microbial communities of the environmental samples were altered during the selective enrichment procedure similarly to the results of Hirooka et al [28]. The microbial community structure of nitrifying enrichments partially reflected the original samples regarding the presence of nitrate-reducing bacteria, and even methanogenic archaea.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Nitrifying bacteria support the growth of heterotrophic bacteria via production of soluble microbial products and biomass decay [51], e.g., in low nutrient containing environments (such as in this study the examined drinking water and nitrifying enrichment samples). However, the microbial communities of the environmental samples were altered during the selective enrichment procedure similarly to the results of Hirooka et al [28]. The microbial community structure of nitrifying enrichments partially reflected the original samples regarding the presence of nitrate-reducing bacteria, and even methanogenic archaea.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding the detection of AOM in nitrifying enrichments by sequenceaided T-RFLP methods, the water networks had autochthonous ammoniaoxidizing communities, which probably originated from the wells. Despite the high detection sensitivity of the PCR method, it has limitations detecting low abundance microorganisms present in diverse population [28] such as drinking water. Regarding the inoculation of enrichments with larger-volume (in our case 45 ml), water samples and the cluster-forming capability of AOB (which otherwise could underestimate the number of AOB) [23,24] could cause the positive results for nitrification in enrichments inoculated with water samples characterized by zero MPN.…”
Section: Discussionmentioning
confidence: 99%
“…In various nitrifying systems, different AOB groups have been found to be dominant under certain prevailing conditions [7,9,21,23] and shifts in AOB population structure have been reported [4,11,12,18] with some affecting nitrification performance [14,16]. It has been suggested that competitive ability and/or tolerance to inhibitors may lead to specific AOB population dominance within nitrifying systems [5,13,17].…”
Section: Introductionmentioning
confidence: 97%